Pengaruh Variabel Makroekonomi terhadap Ekspor Indonesia Pendekatan Model Autoregressive Distributed Lag - Daniel Cristover; Yozi Aulia Rahman (ARBITRASE: Journal of Economics and Accounting, 2025)
This study aims to analyze the influence of Foreign Direct Investment (FDI), inflation, the exchange rate of the rupiah against the US dollar, and the unemployment rate on Indonesia’s exports, based on the theories of Comparative Advantage, Heckscher-Ohlin, Purchasing Power Parity (PPP), and Export Demand Elasticity. Annual time series data from 1990 to 2022 were analyzed using the Autoregressive Distributed Lag (ARDL) model, which can estimate both short- and long-term relationships for variables with different levels of integration. The cointegration test (F-statistic = 7.44 > 3.49) indicates a long-term equilibrium relationship among variables. In the long run, inflation has a significantly positive effect on exports (coefficient = 0.480354; p = 0.0000), while the exchange rate has a significantly negative effect (coefficient = –0.247872; p = 0.0005). Meanwhile, FDI (coefficient = 0.174065; p = 0.1093) and unemployment (coefficient = –0.0000622; p = 0.8779) do not show statistically significant effects. The Error Correction Model shows a CointEq(-1) coefficient of –0.503552 (p = 0.0000), indicating a mechanism of adjustment toward long-run equilibrium. These findings suggest that inflation driven by rising export commodity prices can boost export value, while currency depreciation may hinder exports due to the heavy reliance on imported inputs. Therefore, Indonesia’s export strategy requires structural reforms in investment targeting and labor market efficiency.